Enhanced selectivity and stability towards CO2 reduction of sub-5 nm Au NPs derived from supramolecular assembly. Issue 20 (4th February 2021) - Song, Xianmeng; Cao, Minna; Chen, Ruru; Wang, Huimin; Li, Hongfang; Cao, Rong
Abstract : Au nanoparticles protected by macrocyclic cucurbit[ n ]uril (CB[ n ]) are obtained from supramolecular self-assembly. Attributed to the unique features of CB[ n ], CB[ n ]-Au catalysts present excellent catalytic performance for CO2 electroreduction to CO. Abstract : We report three well-defined types of Au nanoparticles (NPs) protected by rigid macrocyclic cucurbit[ n ]uril (CB[ n ]) (CB[ n ]-Au), which are prepared via the supramolecular self-assembly of the precursors. CB[ n ]-Au shows excellent catalytic activity and selectivity, with a performance that can be maintained for up to 72 h in the electroreduction of CO2 to CO. The effects of the structural features of different CB[ n ]s on the electrocatalytic performance of the Au NPs have been revealed for the first time.